Electronic democracy in Europe : prospects and challenges of E-Publics, E-participation and E-voting - Lindner, Ralf;Aichholzer, Georg;Henne, Leonhard (Switzerland : Cham Springer International Publishing Springer, 2016)
This edited book is the first of its kind to systematically address the intersection of e-democracy and European politics.
Part I: The E-Public in Europe -- Part II: E-Participation -- Part III: E-Voting.
Includes bibliographical references and index.
Keywords: POLITICAL PARTICIPATION -- EUROPE -- COMPUTER NETWORK RESOURCES